Electrospun polylactic acid/date palm polyphenol extract nanofibres for tissue engineering applications - Khadija M. Zadeh (14152338) (2019)
In this study, a set of polylactic acid (PLA)/polyphenol extracted from date palm fruit (DP) blends were prepared by electrospinning process to be used as cell culture scaffolds for tissue engineering applications. For this purpose, PLA/DP blends with variable composition were dissolved in dichloromethane/dimethylformamide (70:30, v/v) mixture and then electrospun to obtain the fibres. Contact angle measurements, dynamic mechanical analysis, mechanical tensile and scanning electron microscopy (SEM) tools were used to study the physico-mechanical properties of the electrospun scaffolds. The results revealed that scaffolds became more hydrophilic with addition of DP. Increasing the polyphenol concentration caused the tensile strength and Young’s modulus to decrease. The SEM graphs indicated a decrease in fibre diameter with increasing DP content. In addition, it was found that both cell proliferation and cell viability were enhanced with increased DP concentration within the scaffolds. The scratch test shows that there is an enhancement in cell migration through the scratch for PLA/DP scaffolds; again, higher DP content resulted better migration. Our results suggest that improved mechanical properties, decreased fibre diameter and enhanced hydrophilicity with addition of DP improved cell migration and cell adhesion for the scaffolds. Overall, these results demonstrate that DP is a potential natural cell-friendly product for tissue engineering applications such as tissue regeneration or wound healing assays. Other Information Published in: Emergent Materials License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s42247-019-00042-8